A New Approach to Analyzing Cycling Stability Using an Inertial Measurement Unit Sensor - Joo, Shinhye; Lee, Gunwoo; Oh, Cheol; Choi, Keechoo (KSCE Journal of Civil Engineering, 2018)
Bicycles are an environment-friendly mode of transport and are leading to more sustainable transportation systems. To increase the use of bicycles as a significant transport mode, a bicycle-friendly roadway environment should be provided. From this perspective, assessment of the roadway environment from the bicyclist viewpoint in terms of safety and comfort is of keen interest. This study explores the cycling stability associated with the roadway environment. An Inertial Measurement Unit (IMU), including an accelerometer and a gyro sensor, were used to determine the factors that influence cycling stability. The acceleration and angular velocity for each axis were obtained from the IMU, which were used to quantify the change in average acceleration of the bicycle and determine the changes in roll, pitch, and yaw of the bicycle. These movements were largely associated with cycling stability. An ordered probit model was adopted to model the relationship between the bicyclist perception and the sensor data representing stability. The estimation results demonstrated that the average angular velocity was statistically significant and affected cycling stability.
Keywords: bikeways; Cycling stability; Environment friendly; Gyro sensors; Inertial measurement unit; Inertial Measurement Unit (IMU); Ordered probit model; Sustainable transportation systems; accelerometer; bicycles; bikeways; cycling stability; gyro sensor; ordered probit model